Two Cinemas: Sierra de Teruel by André Malraux and Birds in Peru by Romain Gary - Hangouët, Jean-François (Literatūra, 2022)
This communication reviews some of the aesthetical and circumstantial characteristics of André Malraux’s only film, Sierra de Teruel (1939), also known as Espoir (Hope, 1945), and of Romain Gary’s first film, Les oiseaux vont mourir au Pérou (Birds in Peru, 1968). As regards Espoir, our observations are based on the 1939 and 1945 versions of the film, now of easy access, and on the abundant and reliable academic literature published about it. Birds in Peru, conversely, is a far lesser-known and lesser-documented work. Screenings of Gary’s film are all too rare indeed nowadays and, but for a few highly specialized references, its appraisal still consists in a short set of irrelevant legends, continually retold by biographers and academics alike despite their blatant discrepancies with historical evidence, with the film itself, and with Gary’s literary works in general. Ours are first-hand observations: in our possession is a release print, which we had digitized and can thus view at will. In addition, we have explored a variety of source materials in cinematographic archives and historical newspapers. Valued either as one of Malraux’s works or as an example of antifascist propaganda, it is lucky that Sierra de Teruel can still be viewed today, despite the political censorship that prevented its release in September 1939 and despite the destruction of all prints but two by the German occupant in France during WWII. Equally fortunate are the facts that moralistic considerations failed to stop the release of Birds in 1968 and that prints of it aren’t all lost. Gary scholars will find food for thought in it, as well as semioticians, Gary’s film being just as allegorical as his contemporary novel The Dance of Genghis Cohn. More generally still, both works, no naïve executions, bring evidence that talented writers can change media effectively. Far from being literal adaptations, their two films narrate free and inspired versions of stories already told in the written form. Their filming style is creative, their technique masterly. Their ease with the cinematographic medium allows them to reemploy and expand devices known to make their personal literary signature. Such as the striking juxtaposition of action and scenery used by Malraux to convey his metaphysics of disjunction between man and nature. Such as the subtle art of immigrating lexical components from other tongues and languages, idiosyncratic to Gary’s novel writing. Even elements of their respective forms of humanism show through their films.